2016
DOI: 10.1016/j.jacc.2016.09.940
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery and the Risk of New-Onset Atrial Fibrillation in Swedish Obese Subjects

Abstract: BACKGROUND Obesity is a risk factor for atrial fibrillation, which in turn is associated with stroke, heart failure and increased all-cause mortality. OBJECTIVE We investigated whether weight loss through bariatric surgery may reduce the risk of new-onset atrial fibrillation. METHODS Swedish Obese Subjects (SOS) is a prospective matched cohort study conducted at 25 surgical departments and 480 primary healthcare centers in Sweden. The cohort was recruited between 1987 and 2001. Among 4021 obese individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(107 citation statements)
references
References 32 publications
6
97
0
4
Order By: Relevance
“…The hazard ratio for the highest quintile of weight loss was 0.70 (95% CI: 0.41–1.18), thus a moderate reduction in risk cannot be excluded based on this trial. Another recent study of obese patients undergoing bariatric surgery found a reduced risk of developing atrial fibrillation with a hazard ratio of 0.71 (95% CI: 0.60–0.83) compared to the control group, providing additional evidence that adiposity is related to increased risk of atrial fibrillation [61]. Our findings of an increased risk of atrial fibrillation with higher hip circumference is somewhat in contrast to previous studies that have found an inverse association between hip circumference and cardiovascular disease [62], however, the inverse associations were only observed after further adjustment for BMI and waist circumference while none of the studies in the current meta-analysis made further adjustments for BMI and waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratio for the highest quintile of weight loss was 0.70 (95% CI: 0.41–1.18), thus a moderate reduction in risk cannot be excluded based on this trial. Another recent study of obese patients undergoing bariatric surgery found a reduced risk of developing atrial fibrillation with a hazard ratio of 0.71 (95% CI: 0.60–0.83) compared to the control group, providing additional evidence that adiposity is related to increased risk of atrial fibrillation [61]. Our findings of an increased risk of atrial fibrillation with higher hip circumference is somewhat in contrast to previous studies that have found an inverse association between hip circumference and cardiovascular disease [62], however, the inverse associations were only observed after further adjustment for BMI and waist circumference while none of the studies in the current meta-analysis made further adjustments for BMI and waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgical intervention in the Swedish Obese Subjects (SOS) cohort study, which involved 2000 surgical patients and 2021 control participants) reduced the risk of AF among individuals under treatment for severe obesity by 29% (95% CI, 0.60‐0.83), although it took several years to occur and was more apparent in younger individuals and in those with HTN. Even more impressive, the reduction occurred despite the less favourable cardiovascular risk‐factor profile at baseline in the surgical group …”
Section: Role Of Obesity In the Pathogenesis Of Atrial Fibrillationmentioning
confidence: 99%
“…Even more impressive, the reduction occurred despite the less favourable cardiovascular risk-factor profile at baseline in the surgical group. 57…”
Section: Role Of Obesity In the Pathogenesis Of Atrial Fibrillationmentioning
confidence: 99%
“…However, epicardial fat is relatively resistant to weight loss regimens; thus, the modest weight loss typically seen with dietary interventions has little effect on epicardial fat deposits, and calorie restriction that leads to a small decrease in weight has minimal effects on AF, diastolic filling abnormalities and HF . In contrast, marked weight loss (by intensive calorie restriction or bariatric surgery) can decrease both the mass and inflammation of epicardial fat, and has reduced the burden of AF and restored sinus rhythm in patients with established AF in both observational studies and randomized trials . Major weight loss also reduces the risk for HF, lessens elevated cardiac filling pressures and diastolic filling abnormalities, and improves symptoms and exercise tolerance in patients with latent or overt HFpEF …”
Section: Therapeutic Challenges In Patients With a Metabolic Disordermentioning
confidence: 99%